Titel prent: Arbeidscontract-Loeff in den Bosch : "Geen knapper volk dan die katholieke arbeiders..." - Hahn, Albert,
Titel prent: Arbeidscontract-Loeff in den Bosch : "Geen knapper volk dan die katholieke arbeiders...".